Users' satisfaction in the use of abstracts and indexes on CD-ROM in selected academic libraries - Marzo, Arlene A. (1995)
This study determined the satisfaction of 323 users after searching the abstracts and indexes on CD-ROM of ten academic libraries: the Ateneo de Manila Rizal Library, the De La Salle University Library, the University of Santo Tomas Main Library, the U.P. Los Baños Main Library, the U.P. Manila University Library and the following University of the Philippines Diliman Libraries; Main Library, College of Education, College of Economics, Institute of Library Science and College of Science Libraries.